2008
DOI: 10.1177/1475921708090560
|View full text |Cite
|
Sign up to set email alerts
|

Impact Damage Detection in Aircraft Composites Using Knowledge-based Reasoning

Abstract: A hybrid reasoning methodology is applied to a complex aerospace structure, and its effectiveness is assessed in identifying and locating the position of impacts. Part of a commercial aircraft wing flap is impacted and time-varying strain response data from the structure are sensed using passive piezoceramic sensors. This structure can be regarded as a small scale version of part of a wing span with the corresponding features being a leading edge and trailing edge. The trailing edge is composed of aluminium sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…Finally, the total average radial error is around 60mm. Results obtained in this work are similar to the ones presented in previous works that used different techniques such as Artificial Neural Networks (LeClerc et al [2007]), Genetic Algorithms (Mahzan et al [2007]) and Case Based Reasoning (Mujica et al [2008]) (Mujica et al [2008]). However, the methodology presented in this work uses the information gathered from the sensors, without computing new or additional features.…”
Section: Analysis Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, the total average radial error is around 60mm. Results obtained in this work are similar to the ones presented in previous works that used different techniques such as Artificial Neural Networks (LeClerc et al [2007]), Genetic Algorithms (Mahzan et al [2007]) and Case Based Reasoning (Mujica et al [2008]) (Mujica et al [2008]). However, the methodology presented in this work uses the information gathered from the sensors, without computing new or additional features.…”
Section: Analysis Results and Discussionsupporting
confidence: 79%
“…Another option is the utilisation of Genetic Algorithms (Mahzan et al [2007]) or Case Based Reasoning combined with different dimensionality reduction (or features extraction) techniques sucha as: Self Organizing Maps -SOM- (Mujica et al [2008]), Principal Component Analysis (PCA), Partial Least Square (PLS), Curvilinear Distance Analysis (CDA) and some extensions of them (Mujica et al [2008]). …”
Section: Methodsmentioning
confidence: 99%
“…Prime examples include research performed into insulating foam strikes following the loss of the space shuttle Columbia [6], approaches involving the use of embedded optical fibres [7,8], and approaches from the non-aerospace sectors, such as pipeline impact detection and monitoring [9]. These approaches have met with much success and now have a wide range of applications in structural health monitoring, extensively validated by experimental results [10,11,12]. Existing methods can be broadly sorted into two fields: fit-from-new, and retro-fit.…”
Section: Acoustic Sensing Conceptsmentioning
confidence: 99%
“…A logic tree then derived which zone the impact was in, based upon a qualitative comparison of the three dt variables. For instance, a comparison of dt 12 and dt 13 can be used to discern if an impact is on the inboard or outboard half of the wing. Various combinations of zones were trialled, and it was found that six overlapping zones, as shown in figure 4, offered reliable and repeatable detection location.…”
Section: Findings Discerning Impact Locationmentioning
confidence: 99%
See 1 more Smart Citation